Blend of aliphatic-aromatic copolyester and polylactic acid, preparation method and application
By preparing a blend of aliphatic-aromatic copolyester and polylactic acid, the problem of insufficient toughness of polylactic acid is solved, and the application in the film bags and packaging fields is improved while maintaining biodegradability.
Patent Information
- Application Number
- CN202510046622.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
Smart Images

Figure CN119823548A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a blend of aliphatic-aromatic copolyester and polylactic acid, a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA) has attracted great attention as an environmentally friendly alternative to traditional petroleum-based polymers because it can be produced from renewable natural resources, is biodegradable, compostable and recyclable after disposal, and is derived from nature and returned to nature. However, so far, these biodegradable polymers have only gained a limited market size, one of the reasons being that PLA has poor toughness compared to traditional oil-based polymers. Considerable efforts have been made to improve the toughness of PLA, such as copolymerization and blending. For example, polyethylene glycol (PEG), polyurethane (PU), epoxidized soybean oil (ESO), poly(ε-caprolactone) (PCL) and polyethylene (PE). Unfortunately, the introduction of these polymers often fails to produce satisfactory reinforcement effects, and some polymers are not biodegradable.
[0003] At present, the tensile strength of pure PLA is 40-70 MPa, but its elongation at break and notched impact strength are only 3-5% and 2-8%, which hinders its application in film bags and packaging to replace petroleum-based plastics. Therefore, in order to meet the needs of sustainable development in today's society, it is necessary to study toughened polylactic acid to expand its application range. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid, the preparation method comprising the following steps:
[0006] S1, in N 2 Under protection, add diacid and diol into the reaction bottle, then add esterification catalyst and stir to carry out esterification reaction to obtain ester exchange prepolymer;
[0007] S2, in N 2 Under protection, a titanium catalyst and a stabilizer are added to the transesterification prepolymer to carry out a polycondensation reaction to obtain an aliphatic-aromatic copolyester PTFB;
[0008] S3. After blending the aliphatic-aromatic copolyester PTFB and polylactic acid on a micro extruder, injection molding is performed using a micro injection molding machine to obtain a blend of the aliphatic-aromatic copolyester and polylactic acid.
[0009] Furthermore, the molar ratio of the diacid to the diol is 1:(1-1.5), the diacid comprises fumaric acid and terephthalic acid, and the molar ratio of fumaric acid to terephthalic acid is 1:(1-7), the diol comprises polyethylene glycol and diol B, and the molar ratio of polyethylene glycol to diol B is 1:(30-35), the molecular weight of the polyethylene glycol PEG raw material is 400-6000 g / mol, the added amount of the esterification catalyst is 0.04-0.08% of the total mass of the acid; the added amounts of the titanium-based catalyst and the stabilizer are 0.02-0.1% and 0.005-0.02% of the total mass of the acid.
[0010] Furthermore, the diol B is one or more of ethylene glycol, diethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 2,3-hexanediol, 2,4-pentanediol, 2,5-hexanediol, and 1,8-octanediol.
[0011] Furthermore, the esterification catalyst in S1 is one or more of tri-n-butyl methoxytin, stannous chloride, stannous octoate, dibutyltin oxide, antimony trioxide, and germanium dioxide.
[0012] Furthermore, the titanium-based catalyst is one or more of tetrapropyl titanate, isopropyl titanate, ethyl titanate, tetrabutyl titanate, tetra-tert-butyl titanate, and titanium dioxide.
[0013] Furthermore, the stabilizer in S2 is one or more of triphenyl phosphate, tricresyl phosphate, dimethyl sulfate, diethyl sulfate, dimethyl borate, diethyl borate, maleic anhydride, stearate, and 4-methoxyphenol.
[0014] Furthermore, the polycondensation reaction temperature in S2 is 200-240° C., the vacuum degree is 50-200 Pa, and the reaction time is 4-10 h.
[0015] Furthermore, in step S3, the extrusion temperature of the extruder is 170-220°C, and the screw speed is 10-200 rpm; the furnace temperature of the injection molding machine is 180-220°C, the mold temperature is 20-50°C, the injection pressure is 700-900 bar, the injection time is 5-15 seconds, the holding pressure is 400-450 bar, and the holding time is 5-15 seconds.
[0016] A blend of aliphatic-aromatic copolyester and polylactic acid is prepared by the above-mentioned method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid.
[0017] The above-mentioned blend of aliphatic-aromatic copolyester and polylactic acid is used in the field of film bags and packaging.
[0018] Beneficial effects of the present invention: The aliphatic-aromatic copolyester / polylactic acid blend provided by the present invention has toughness exceeding that of pure polylactic acid and is biodegradable. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 Schematic diagram of the synthesis of aliphatic-aromatic copolyesters in the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 137.16 g of terephthalic acid, 15.24 g of fumaric acid, 87.6 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.092g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was carried out for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 95 parts of polylactic acid and 5 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 54.9MPa, elongation at break 118.2%, notched impact strength 14.8J / m 2 .
[0024] Example 2
[0025] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 137.16 g of terephthalic acid, 15.24 g of fumaric acid, 87.6 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.092g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was carried out for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 90 parts of polylactic acid and 10 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 49.1MPa, elongation at break 201.2%, notched impact strength 29.7J / m 2 .
[0026] Example 3
[0027] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 137.16 g of terephthalic acid, 15.24 g of fumaric acid, 87.6 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.092g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was performed for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 85 parts of polylactic acid and 15 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 40.6MPa, elongation at break 276.9%, notched impact strength 40.8J / m 2 .
[0028] Example 4
[0029] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 120 g of terephthalic acid, 30 g of fumaric acid, 90 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.09g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was performed for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 95 parts of polylactic acid and 5 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 47.3MPa, elongation at break 104.7%, notched impact strength 20.9J / m 2 .
[0030] Example 5
[0031] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 120 g of terephthalic acid, 30 g of fumaric acid, 90 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.09g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was performed for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 90 parts of polylactic acid and 10 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 43.4MPa, elongation at break 178.4%, notched impact strength 32.8J / m 2 .
[0032] Example 6
[0033] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 120 g of terephthalic acid, 30 g of fumaric acid, 90 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.09g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.076g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was performed for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 85 parts of polylactic acid and 15 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 33.7MPa, elongation at break 249.2%, notched impact strength 47.2J / m 2 .
[0034] Example 7
[0035] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 103.4 g of terephthalic acid, 44.32 g of fumaric acid, 92.28 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.088g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.074g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was performed for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 95 parts of polylactic acid and 5 parts of aliphatic-aromatic copolyester were dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 40.8MPa, elongation at break 62.5%, notched impact strength 13.2J / m 2 .
[0036] Example 8
[0037] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 103.4 g of terephthalic acid, 44.32 g of fumaric acid, 92.28 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.088g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.074g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was carried out for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 90 parts of polylactic acid and 10 parts of aliphatic-aromatic copolyester were taken and dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 36.5MPa, elongation at break 126.9%, notched impact strength 25.4J / m 2 .
[0038] Example 9
[0039] In a four-necked flask equipped with a dehydrator, a mechanical stirrer and a nitrogen purge port, 103.4 g of terephthalic acid, 44.32 g of fumaric acid, 92.28 g of 1,4-butanediol and 160 g of polyethylene glycol (Mn = 2000 g / mol) were added. 2 Replace 3 times and continue to introduce appropriate N 2Flow, when the oil bath temperature rises to 185℃, start mechanical stirring, add 0.088g antimony trioxide to the system, react for a period of time, collect the distilled water through the dehydration device, and end the reaction until the water produced is close to the theoretical value to obtain an ester exchange prepolymer. Subsequently, 0.074g tetrabutyl titanate, 0.015g 4-methoxyphenol and 0.015g triphenyl phosphate were added to the system, the temperature was raised to 240℃, the vacuum system was turned on, the pressure was reduced to about 60Pa, and the reaction was carried out for 6h to obtain aliphatic-aromatic copolyester PTFB. In parts by weight, 85 parts of polylactic acid and 15 parts of aliphatic-aromatic copolyester were taken and dried in a vacuum oven at 60℃ for 12 hours to ensure that the influence of moisture was eliminated. The dried sample was added to the extruder for extrusion granulation. Before extrusion, it was mixed with a twin-screw inner circulation for 5min. The extrusion temperature of the extruder was 180℃ and the screw speed was 50rpm. The above particles were added to the injection molding machine to press the polylactic acid blend strips. The furnace temperature of the injection molding machine was 195°C, the mold temperature was 30°C, the injection pressure and time were 800 bar, 10 seconds, and the holding pressure and time were 400 bar, 8 seconds. Its mechanical properties are as follows: tensile strength 27.9MPa, elongation at break 192.3%, notched impact strength 38.1J / m 2 .
[0040] Comparative Example 1
[0041] Pure polylactic acid particles in the example were injected into test specimens. The mechanical properties were as follows: tensile strength 64.7 MPa, elongation at break 3.5%, notched impact strength 2.2 J / m 2 .
[0042] It can be seen from Comparative Example 1 and Examples 1-9 that the toughness of the aliphatic-aromatic copolyester / polylactic acid blend prepared by the present invention exceeds that of pure polylactic acid and is biodegradable. When the addition amount of the aliphatic-aromatic copolyester is 10%, the tensile strength retention rate is 76%, and the elongation at break increases by 58 times.
[0043] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0044] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid, characterized in that: The preparation method comprises the following steps: S1. Under N2 protection, add diacid and diol into a reaction bottle, then add esterification catalyst and stir to carry out esterification reaction to obtain ester exchange prepolymer; S2. Under the protection of N2, adding a titanium catalyst and a stabilizer to the transesterification prepolymer for polycondensation reaction to obtain aliphatic-aromatic copolyester PTFB; S3. After blending the aliphatic-aromatic copolyester PTFB and polylactic acid on a micro extruder, injection molding is performed using a micro injection molding machine to obtain a blend of the aliphatic-aromatic copolyester and polylactic acid.
2. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The molar ratio of the diacid to the diol is 1:(1-1.5), the diacid comprises fumaric acid and terephthalic acid, and the molar ratio of fumaric acid to terephthalic acid is 1:(1-7), the diol comprises polyethylene glycol and diol B, and the molar ratio of polyethylene glycol to diol B is 1:(30-35), the molecular weight of the polyethylene glycol PEG raw material is 400-6000 g / mol, the added amount of the esterification catalyst is 0.04-0.08% of the total mass of the acid; the added amounts of the titanium catalyst and the stabilizer are 0.02-0.1% and 0.005-0.02% of the total mass of the acid.
3. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The diol B is one or more of ethylene glycol, diethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 2,3-hexanediol, 2,4-pentanediol, 2,5-hexanediol and 1,8-octanediol.
4. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The esterification catalyst in S1 is one or more of tri-n-butyltin methoxide, stannous chloride, stannous octoate, dibutyltin oxide, antimony trioxide, and germanium dioxide.
5. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The titanium-based catalyst is one or more of tetrapropyl titanate, isopropyl titanate, ethyl titanate, tetrabutyl titanate, tetra-tert-butyl titanate, and titanium dioxide.
6. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The stabilizer in S2 is one or more of triphenyl phosphate, tricresyl phosphate, dimethyl sulfate, diethyl sulfate, dimethyl borate, diethyl borate, maleic anhydride, stearate, and 4-methoxyphenol.
7. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: The polycondensation reaction temperature in S2 is 200-240° C., the vacuum degree is 50-200 Pa, and the reaction time is 4-10 hours.
8. The method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to claim 1, characterized in that: In step S3, the extrusion temperature of the extruder is 170-220° C., and the screw speed is 10-200 rpm; the furnace temperature of the injection molding machine is 180-220° C., the mold temperature is 20-50° C., the injection pressure is 700-900 bar, the injection time is 5-15 seconds, the holding pressure is 400-450 bar, and the holding time is 5-15 seconds.
9. A blend of aliphatic-aromatic copolyester and polylactic acid, characterized in that: The blend of aliphatic-aromatic copolyester and polylactic acid is prepared by the method for preparing a blend of aliphatic-aromatic copolyester and polylactic acid according to any one of claims 1 to 8.
10. Use of the blend of aliphatic-aromatic copolyester and polylactic acid as claimed in claim 9 in the field of film bags and packaging.